A meta-frontier approach to measure productivity differences of domestic and foreign affiliated firms - Tunca, Halil; Karaçuka, Mehmet; Çatik, A. Nazif (Journal of Business Economics and Management, 2013)
This paper aims to evaluate the performance of foreign affiliated and domestic firms in Turkish manufacturing subsectors covering the period 1992 and 2001. Due to the heterogeneity between domestic and foreign affiliated firms in terms of technology level, we construct a meta-frontier model to measure relative efficiency and technology gap ratios (TGR's) of domestic and foreign affiliated firms. We find that technical efficiencies of foreign affiliated firms are higher than domestic firms, and display a stable pattern during the investigation period. However; technology gap ratios indicate the existence of a negative relationship between the TGR's and technical efficiency of the firms in domestic subsectors. This means that technically efficient firms are in fact using the low level of technology. However the results do not indicate any significant relationship between the technical efficiency and TGR's of foreign affiliated firms.First published online: 12 Sep 2012